Effects of Arbuscular Mycorrhiza Fungi and Coffee Pulp Compost in Improving Soil Water Uptake by Chilli Around the Permanent Wilting Point Conditions - Ingri Dayana; Bandi Hermawan; Yudhi Harini Bertham; Dwi Wahyuni Ganefianti (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2020)
Soil water availability to the plants is a range of water content between the field capacity and the permanent wilting point (PWP) conditions. The PWP is defined as the lower limit of soil water content that the plant can extract water from the soil as indicated by the symptoms of wilting plants. This is because plant roots are unable to penetrate the soil micropores that contain the water. The study aims to analyze the effects of arbuscular mycorrhizal fungi (AMF) and compost in enhancing soil water absorption by the plant when the water content is close to the permanent wilting point. Four doses of AMF (0, 5, 10 and 15 g.plant-1) and three doses of coffee pulp-made compost (0, 5 and 10 ton.ha-1) were arranged according to a randomized complete block design with three replicates. Results showed that the application of AMF significantly enabled the plant to improve water uptake when the soil water content was about at the permanent wilting point conditions. The AMF addition of 15 g.plant-1 significantly prolonged the growing period of chili to wither and the plant showed the wilting symptoms at the soil water content of 5 to 7% lower than the no-AMF plants. Improved water uptake under water stress conditions was attributed to increases in the root colonization by AMF.